Quantification of volatile metabolites in exhaled breath by selected ion flow tube mass spectrometry, SIFT-MS - Španěl, Patrik; Smith, David (Clinical mass spectrometry (Del Mar, Calif.), 2020)
Selected ion flow tube mass spectrometry, SIFT-MS, is a non-separative method for direct quantitative analyses of volatile compounds, VOCs, in air and humid breath based on chemical ionization. Selected reagent ions, either H3O+, NO+ or O2 + (non-reactive with major components of air), ionize analyte molecules during a defined time in a flow tube by ion-molecule reactions thus producing analyte ions that are characteristic of the neutral analyte VOCs. Concentrations can be calculated in real-time from the ion count rates. Direct on-line analysis of single or multiple breath exhalations or off-line analysis of breath samples collected into bags can be performed. Several volatile breath metabolites have been quantified by SIFT-MS, including ammonia, acetone, hydrogen cyanide, alcohols, pentane, acetic acid, methane, and sulphur compounds. Their potential as biomarkers is discussed.
Keywords: SIFT-MS; Breath VOCs; Metabolites; Biomarkers